Impact of Firm Specific Factors on Financial Performance of Life Insurance Companies in Nepal - Hamal, Janga Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2020)
The financial performance of life insurance companies determines the company’s ability to generate revenues and manage assets, liabilities and the financial interests of its stakeholders. However, there are limited studies discoursing major determinants of companies’ financial performance. To fulfill the gap, this study aimed to determine the effects of various firm-specific factors - firm size, liquidity ratio, short-term debt, long-term investment and firm age - on financial performance of life insurance companies in Nepal. The dependent variables influencing financial performance considered were return on assets (ROA) and return on equity (ROE). The study was based on secondary data of seven life insurance companies studied over a period of ten years, from 2009/10 to 2018/19. The data were collected from the financial statements published annually by the selected life insurance companies, Insurance Board of Nepal and Nepal Stock Exchange. In order to derive the impacts of firm-specific variables on ROA and ROE, descriptive statistics, correlation analysis and regression models were used. The study identified size and long-term investment to have negative and statistically significant relationship with financial performance. It also showed that higher the age of the company, the more difficult it will be to accumulate profit. The most influencing factors for the financial performance in Nepalese life insurance companies were firm size and long-term investment. Whereas, the explanatory power of liquidity seemed feeble. The findings elucidated that over-investment in long-term investments should be critically considered as it can have adverse effect on future profitability of the companies. Similarly, life insurance companies should increase their size only after careful examination over financial performance as it can result in diseconomies of scale and reduce the firm’s profitability.